2012
DOI: 10.1038/jes.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to arsenic, AS3MT polymorphism and prevalence of diabetes in Mexico

Abstract: Exposure to arsenic in drinking water is associated with increased prevalence of diabetes. We previously reported an association of diabetes and urinary concentration of dimethylarsinite (DMAsIII), a toxic product of arsenic methylation by arsenic ( +3 oxidation state) methyltransferase (AS3MT). Here we examine associations between AS3MT polymorphism, arsenic metabolism and diabetes. Fasting blood glucose, oral glucose tolerance and self-reported diagnoses were used to identify diabetic individuals. Inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…The trivalent species MAs(III), DMAs(III) and TMAs(III) are intermediates but not products. Most consistent with this hypothesis is that humans primarily excrete DMAs(V) and to a lesser extent MAs(V), but, until recently, little or no trivalent arsenicals were found in urine (12, 13). More recently, Hayakawa and coworkers (9) proposed an alternate pathway in which the preferred substrates of the methyltransferase are the glutathione (GSH) conjugates As(GS) 3 and MAs(GS) 2 , and the products are the trivalent conjugates MAs(GS)2 and DMAs(GS).…”
mentioning
confidence: 84%
“…The trivalent species MAs(III), DMAs(III) and TMAs(III) are intermediates but not products. Most consistent with this hypothesis is that humans primarily excrete DMAs(V) and to a lesser extent MAs(V), but, until recently, little or no trivalent arsenicals were found in urine (12, 13). More recently, Hayakawa and coworkers (9) proposed an alternate pathway in which the preferred substrates of the methyltransferase are the glutathione (GSH) conjugates As(GS) 3 and MAs(GS) 2 , and the products are the trivalent conjugates MAs(GS)2 and DMAs(GS).…”
mentioning
confidence: 84%
“…Genetic polymorphisms have been identified which modify associations between air pollutants PM 10 , O 3 , NO 2 and insulin resistance in a Korean population [183]. Other genetic polymorphisms have been identified which lead to differences in arsenic metabolism [41], and which may increase susceptibility to toxic effects of arsenic exposure [184][185][186][187].…”
Section: Identification Of Susceptible Populationsmentioning
confidence: 99%
“…Multiple studies have found that differences in the metabolism of inorganic arsenic and the distribution and excretion of arsenic metabolites are associated with likelihood of diabetes development [12,[57][58][59][60]. As detailed previously, inorganic arsenic is methylated primarily by AS3MT to form the monomethylated and dimethylated arsenic metabolites, MAs and DMAs.…”
Section: Genetic and Epigenetic Underpinnings For Arsenic-associated Dmmentioning
confidence: 99%
“…Studies of arsenic-exposed populations have found that higher inorganic arsenic and MAs in urothelial cells and higher DMAs in urine are more strongly associated with DM than drinking water measures of arsenic or U-tAs [44,59,[61][62]. These differences in arsenic metabolite profiles represent a potential indicator of the risk of developing DM and could be mediated by differences in genotypes, specifically single nucleotide polymorphisms (SNPs), of critical genes such as AS3MT [63], CAPN-10 -a calcium-dependent protease that plays a key role in exocytosis of insulin-containing vesicles in β-cells [64], GSTO1 -an enzyme that contributes to the reduction of arsenic from the pentava-future science group Arsenic-associated diabetes & the epigenome Special Report lent to trivalent form [57] and NOTCH2 -a member of a signaling cascade involved in cell differentiation [57][58][64][65]. Interestingly, the majority of SNPs associated with differences in arsenic metabolism occur in noncoding regions of the genes, suggesting a potential role for regulatory factors or splice variants.…”
Section: Genetic and Epigenetic Underpinnings For Arsenic-associated Dmmentioning
confidence: 99%